Research Work for Students: Its Peculiarities at Ukrainian Higher Education Institutions in the Conditions of Martial Law - Shunevych, Bohdan (International Journal of Advanced Corporate Learning (iJAC), 2024)
The paper presents analysis of two ways for organizing the research work for students at the Department of Foreign Languages in Lviv National Environmental University: a) the use of modern technologies, robotization of production processes abroad and in Ukraine; b) educational material researched by students from massive open online courses platforms, other electronic resources for students as additional educational materials to the main ones proposed by teachers for the taught disciplines. There are also considered some electronic educational materials implemented for students and discussed by professors of different Ukrainian higher educational institutions at teachers’ conferences as well as the ways of spreading the results of students research work and exchanging their experience in usage of the reviewed materials are proposed. Under martial law, the research work for students of higher education institutions of Ukraine should be brought to a new level, especially in the military sphere and for helping our people to quickly restore all spheres of the national economy destroyed during the Russian-Ukrainian war. The results of the students research can be used by the teaching staff for planning and improving the educational process at our and other universities.